Skutki przeobrażeń organizacji a funkcja personalna - wybrane zagadnienia - Antczak, Zbigniew (The consequence of transformation in organizations and personnel function (HRM), 2007)
The author presents the consequences of transformation in companies. Following these changes among other things of personnel function (Human Resources Management) the laboured flexible forms of employment contract were revised.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 175-186